The Academic Buoyancy Based on Temperament Personality Types - andia kusuma; Siti Maliha; Diyah Putri Asari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
Academic buoyancy refers to students’ ability to cope with, overcome, and recover from everyday academic challenges. This capability is particularly important for junior high school students who are experiencing developmental transitions accompanied by increasing academic demands. The present study aimed to examine differences in academic buoyancy based on temperament personality types among students in private Islamic junior high schools in Malang City. This study employed a quantitative approach with a comparative research design. Participants consisted of 103 seventh- and eighth-grade students selected through purposive sampling. Data were collected using an Academic Buoyancy Scale developed from Martin’s theory and a temperament personality scale based on the Hippocrates-Galenus typology developed by Florence Littauer. Data were analyzed using One-Way Analysis of Variance (ANOVA). The findings revealed significant differences in academic buoyancy across temperament personality types. Students with a Choleric temperament demonstrated higher academic buoyancy than those with a Melancholic temperament. These findings indicate that temperament characteristics play an important role in students’ ability to manage everyday academic challenges. Therefore, educational and counseling services should consider students’ temperament characteristics when designing interventions to enhance academic buoyancy.